Pertumbuhan bibit kopi Liberika terhadap inokulasi mikoriza pada media tanam lahan marginal dalam polybag - Lizawati, Lizawati; Kartika, Elis; Duaja, Made Deviani; Gusniwati, Gusniwati (Proceedings Academic Universitas Jambi, 2025)
Liberica coffee has a potential for cultivation on sub-optimal lands such as peat, ultisol, and post-coal mining soils. However, nutrient deficiencies, extreme pH, and low soil microbial activity often become challenges during the seedling phase, which can play a crucial role in determining the success of the plant growth in the field. To address these obstacles, this research aims to optimize the adaptation of Liberica coffee seedlings in various sub-optimal growing media through the application of mycorrhizae. The experiment was conducted using a group of randomized factorial with two treatment factors: (1) mycorrhizal inoculation (without mycorrhizae and with mycorrhizae) and (2) types of sub-optimal growing media at six levels (peat soil, ultisol soil, post-coal mining soil, peat and ultisol mixture at a 1:1 ratio, peat and ultisol mixture at a 2:1 ratio, and peat and ultisol mixture at a 1:2 ratio). The three-month-old Liberica coffee seedlings were used as planting material. The observed variables included plant height increment, number of leaves, stem diameter, and number of branches. The results showed that, at two months after treatment, no significant effect of the treatments was observed on the growth of Liberica coffee seedlings.